Inheritance and Quantitative Trait Locus Mapping of Fusarium Wilt Resistance in Cucumber - Dong, Jingping; Xu, Jun; Xu, Xuewen; Xu, Qiang; Chen, Xuehao (Frontiers in Plant Science, 2019)
Fusarium wilt (FW) is a very serious soil-borne disease worldwide, which usually results in a huge loss of yield in cucumber production. To date, it is still maintains unknown on the inheritance and molecular mechanism to FW of cucumber. In this study, two inbred lines ‘Superina’ (P1) and ‘Rijiecheng’ (P2) were used as the sensitive line and the resistant line, respectively. A mixed major gene plus polygene inheritance model was used to analyze the resistance to FW in cucumber with P1, P2, F1, B1, B2 and F2 generations, and finally genetic model E-1 was chosen as the best-fitting one. The major effect QTL (fw2.1) was determined at 0-1.91Mb in physical location of Chr2 by bulked-segregant analysis (BSA). To make the fine mapping of fw2.1, we used 5 InDel markers to narrow down the fw2.1 to 0.60 Mb interval, which is located at physical sites 1248093 to 1817308 totally contained 80 candidate genes. Also we used the transcriptome data of Rijiecheng inoculating with Fusarium oxysporum f. sp. cucumerinum (Foc) to screen the candidate genes, and finally 12 differentially expressed genes in fw2.1 were determinated. Five out of those 12 genes were significantly induced by the FW, and the expression levels of them in the resistant line Rijiecheng inoculated by Foc were higher than that by water (CK). Our results may help to better understand the genetic basis and provide valuable information for obtaining the key FW resistance genes in cucumber in the future.